Antifungal activity from fruit peel extracts / Nurul Syazwani Razali - Razali, Nurul Syazwani (2017)
Antifungal drug from natural resources such as vegetables and fruits are more safety and environmental friendly than synthetic drugs. The aim of this study is to evaluate the antifungal activity from methanolic and chloroform extract of Citrullus lanatus, Cucumis melo var. inodorus, and Cucumis melo var. cantalupensis against Rhizopus stolonifer, Aspergillus niger, Candida albicans and Saccharomyces sp. and to screen the phytochemical compounds that present in the fruit peel extracts using Thin Layer Chromatography (TLC) technique. The antifungal activity was evaluated from the crude extracts by disc diffusion method. The phytochemical compounds present in the crude extracts were screened by TLC. From the result, the methanolic and chloroform extract of fruits peel had no antifungal activity against R. stolonifera, A. niger, C. albicans and Saccharomyces sp. Only the positive control (fluconazole) shows the inhibition zone, which is the highest value is 37.67 ± 0.58 against Saccharomyces sp.. Based on TLC, methanolic extract have higher retention factor (Rf) value than chloroform extract. The compound that present on the TLC plate is chlorophyll.